Research Overview and Development of Impatiens L.: A Bibliometric Analysis (1987–2023) - Yuan Chen; Jiarui Zhu; Ling Wang; Peng Ning; Weixia Huang; Zhuoran Zou (Horticulturae)
Impatiens L. plants have a variety of flower colors, abundant flowers, and unique flower types, which have high ornamental and medicinal value. This paper utilized CiteSpace (version 6.2.R4) and VOSviewer (version 1.6.20) software to analyze documents related to Impatiens L. research from 1987 to 2023, sourced from the Web of Science database (WOS) and the China National Knowledge Infrastructure (CNKI). Bibliometric analyses were conducted to explore the literature potential of Impatiens L. research, revealing publication volume, discipline distribution, major research institutions and researchers, research hotspots, and research trends. The results indicated a consistent increase in articles published on Impatiens L., with the United States, China, and India as the primary research countries. The research direction predominantly focused on plant science, ecology, and horticulture, with universities and research institutes being the main contributors. The Chinese Academy of Sciences and Florida State University were identified as having the most published articles and a strong influence. Research on Impatiens L. primarily focused on investigating new species, phenotypic plasticity, biodiversity, and systematic classification. Future efforts should emphasize the investigation and protection of Impatiens L. resources, conduct in-depth research on the plant’s active components, innovate breeding technology, and explore the biological characteristics and ecological role of Impatiens L. through interdisciplinary collaboration.